Bioethical Concerns During the COVID-19 Pandemic: What Did Healthcare Ethics Committees and Institutions State in Spain? - Ruiz-Hornillos, Javier; Hernández Suárez, Pilar; Marín Martínez, Juana María; Miguel Beriain, Íñigo de; Nieves Vázquez, María Auxiliadora; Albert, Marta; Herrera Abián, María; Pacheco-Martínez, Pedro A.; Trasmontes, Victoria; Guillén-Navarro, Encarna (Frontiers in Public Health, 2021)
Objectives Each new wave of the COVID-19 pandemic invites the possible obligation to prioritize individuals’ access to vital resources, and thereby leads to unresolved and important bioethical concerns. Governments have to make decisions to protect access to the health system with equity. The prioritization criteria during a pandemic are both a clinical and legal-administrative decision with ethical repercussion. We aim to analyse the prioritization protocols used in Spain during the pandemic which, in many cases, have not been updated. Method We carried out a narrative review of 27 protocols of prioritization proposed by healthcare ethics committees, scientific societies and institutions in Spain for this study. The review evaluated shared aspects and unique differences and proffered a bioethical reflection. Results The research questions explored patient prioritization, the criteria applied and the relative weight assigned to each criterion. There was a need to use several indicators, being morbidity and mortality scales the most commonly used, followed by facets pertaining to disease severity and functional status. Although age was initially considered in some protocols, it cannot be the sole criterion used when assigning care resources. Conclusions In COVID-19 pandemic there is a need for a unified set of criteria that guarantees equity and transparency in decision-making processes. Establishing treatment indications is not the aim of such criteria, but instead prioritizing access to care resources. In protocols of prioritization, the principle of efficiency must vary according to the principle of equity and the criteria used to guarantee such equity.